Voltage resonant inverter as a power source - Lupenko, Anatoliy; Stakhiv, Petro (Publishing House of Lviv Polytechnic National University, 2014)
The operation mode of a voltage resonant inverter as a power source with variable load is analyzed. In order to reduce load power variations, an approach to development of the inverter’s load power response based on providing similar positive and negative power deviations from its nominal value has been proposed. The design procedure for resonant inverter with open loop structure as a power source has been elaborated. For a high pressure sodium lamp as a load, the power deviation of about 4% from its nominal power in case of two fold increase of the lamp resistance thriughout its lifetime has been achieved. Проаналізовано режим роботи резонансного інвертора напруги на змінне навантаження, близький до режиму джерела потужності. Для зменшення варіації потужності в навантаженні запропоновано метод формування потужнісної навантажувальної характеристики резонансного інвертора шляхом забезпечення однакових додатних та від’ємних відхилень його потужності від номінального значення. Розроблено методику розрахунку резонансного інвертора з розімкненою структурою як джерела потужності. На прикладі натрієвої лампи високого тиску як навантаження отримано відхилення потужності 4% від номінальної за двократної зміни опору лампи впродовж всього строку її служби.
Резонансний інвертор напруги як джерело потужності
Keywords: voltage resonant inverter; power source; high frequency operation; variable load resistance